1983
DOI: 10.1007/bf02779916
|View full text |Cite
|
Sign up to set email alerts
|

Food microbiology update emerging foodborne pathogens

Abstract: A review of three "emerging" foodborne pathogen groups is presented, including Campylobacter jejuni/coli, Yersinia enterocolitica, and foodborne Vibrio sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…). Campylobacter was recognized as an emerging foodborne pathogen relatively recently (Bryant ), and research conducted on strategies to reduce Campylobacter in food animals has mostly been conducted in the past 10 years (Newell et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Campylobacter was recognized as an emerging foodborne pathogen relatively recently (Bryant ), and research conducted on strategies to reduce Campylobacter in food animals has mostly been conducted in the past 10 years (Newell et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Carcass contamination is correlated to intestinal colonization, and it is estimated that a 2 log 10 reduction in intestinal Campylobacter would decrease the human risk of infection by 30-fold (Van Deun et al 2008). Campylobacter was recognized as an emerging foodborne pathogen relatively recently (Bryant 1983), and research conducted on strategies to reduce Campylobacter in food animals has mostly been conducted in the past 10 years (Newell et al 2011). Efforts in reducing Campylobacter have largely been directed towards biosecurity improvement and in-feed/water additives like phages, bacteriocins, pre-and probiotics, organic acids (OA) and botanicals, but none of them, alone, was proven to be completely effective, reliable and reproducible (Lin 2009;Hermans et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter jejuni is a Gram‐negative, microaerophilic food‐borne pathogen and a leading cause of acute bacterial gastroenteritis in humans (Bryant, 1983; Altekruse et al ., 1999). It colonizes the intestinal tract of many warm‐blooded animals (Svedhem and Kaijser, 1981) and is commensal in poultry, cattle and swine (Harris et al ., 1986; Kazwala et al ., 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that workers at the U.S. Food and Drug Administration have suggested an in-the-can pasteurizing process for canned oysters. Their preliminary results indicate an effective temperature and time of 15 to 30 min at 57.2°C (7). Wilson and Ashley (41) reported that the bacteria are killed by heat at 55°C in 15 min.…”
mentioning
confidence: 97%
“…The exposure of V. cholerae for 15 min at 55°C, 10 min at 60°C, or 5 min at 65°C was reported to kill the organisms (15, 32, 41). These temperature-time relationships were found not to hold when different foods were contaminated with these organisms (C. A. Makukutu, Masters of Public Health thesis, University of Texas, Houston, 1983 Food can become contaminated with V. cholerae from food handlers who are infected or from convalescent or asymptomatic carriers (5,7,16,28,32,35,44; C. 0. Tacket, Letter, J.…”
mentioning
confidence: 99%